In vitro activity of eight antimicrobial agents against non-penicillinase-producing gonococci isolated in Munich. Issue 4 (August 1988) - Abeck, D; Johnson, A P; Alexander, F; Korting, H C; Ballard, R C
Abstract : The susceptibility of 119 strains of Neisseria gonorrhoeae isolated in Munich in 1986 to eight antibiotics was assessed. Although some degree of resistance to penicillin and tetracycline, as well as high minimum inhibitory concentrations (MIC) of spectinomycin, were observed, all the strains were sensitive to ciprofloxacin, enoxacin, fleroxacin, cefotaxime, and FCE 22250.